Harmonic radiation of a relativistic nonlinear inverse Compton scattering using two laser wavelengths - Y. Sakai; O. Williams; G. Andonian; A. Fukasawa; E. Hemsing; A. Marinelli; S. Barber; F. H. O’Shea; J. B. Rosenzweig (Physical Review Special Topics. Accelerators and Beams, 2011)
The use of two different wavelength lasers in the nonlinear regime of the inverse Compton scattering interaction is proposed in order to provide a new strategy for controlling scattered photon energy distributions in the x-ray to γ-ray spectral region. In this nonlinear interaction, the component of the relativistic electron’s trajectory driven by a longer-wavelength laser with the normalized vector potential a_{L}∼1 is a large oscillatory figure-8; in the proposed scenario a rapid small-amplitude oscillation induced by a shorter-wavelength laser is superimposed upon this figure-8. Thus, the electron’s momentum is mainly supplied from longer-wavelength laser, while the high-frequency part of the acceleration is given by shorter-wavelength laser. In this way, the harmonics radiated at high frequency from the oscillating electron can be strongly modified by the nonlinear motion initiated by the low frequency, large a_{L} laser resulting in the generation of the harmonics with the photon energy of 4γ^{2}h̵(ω_{L,short}+nω_{L,long}). In this paper, the electron’s kinetics in the two-wavelength laser field and the concomitant emitted radiation spectrum are examined, with numerical illustrations based on a classical Lienard-Wiechert potential formalism provided.